Peran Literasi Dalam Mengembangkan Minat Baca dan Meningkatkan Berpikir Kritis - Arva Dzukfikar; Imam Ismawan; Indan Fitriani; Sarbini (ANNAHDLIYAH: Jurnal Manajemen Pendidikan Islam, 2025)
This research aims to describe the role of the literacy program in developing students' reading interest and critical thinking skills at SD Negeri 1 Wonomulyo, and to analyze the contribution of KKN students in supporting the success of the program. The approach used is qualitative with a descriptive method thru interviews, observations, and documentation of school principals, teachers, and students. The research results show that literacy activities such as reading habits, mobile libraries, and discussions are able to significantly increase students' reading interest and critical thinking skills. The active role of KKN students in designing and implementing literacy activities has proven effective in creating a sustainable reading culture and a conducive learning environment. Despite facing obstacles such as limited facilities and monotonous teaching methods, innovative and collaborative strategies were able to overcome these constraints. This result confirms that literacy plays a central role in the development of students' competencies and character, and serves as an important foundation for building their critical and analytical abilities